2019
DOI: 10.1016/j.cej.2018.12.122
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of ferric groundwater treatment residuals for inorganic-organic hybrid biosorbent preparation and its use for vanadium removal

Abstract: Utilization of ferric groundwater treatment residuals for inorganic-organic hybrid biosorbent preparation and its use for vanadium removal, Chemical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 52 publications
(70 reference statements)
2
21
0
Order By: Relevance
“…This confirmed that Fe–O and Fe–OH groups acted as the adsorption sites. Slight shifts of the Fe 2p 3/2 and Fe 2p 1/2 peaks towards a higher binding energy were also found earlier by Zhang et al. (2019) for the ferric water treatment residuals after the adsorption of vanadium.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This confirmed that Fe–O and Fe–OH groups acted as the adsorption sites. Slight shifts of the Fe 2p 3/2 and Fe 2p 1/2 peaks towards a higher binding energy were also found earlier by Zhang et al. (2019) for the ferric water treatment residuals after the adsorption of vanadium.…”
Section: Resultssupporting
confidence: 79%
“…The O 1s spectrum of SG dye adsorbed GWTW shows that BE of oxygen of the hydroxy group decreased after the dye adsorption. This change can be due to the interaction between the hydroxyl groups of GWTW and SG dye anions ( Zhang et al., 2019 ). There are two peaks in high – resolution Ca 2p spectra (Figure 3S) at 347.52 (2p 3/2 ) and 351.22 eV (2p 1/2 ), which can be attributed to CaCO 3 ( Li and Zeng, 2012 ; Ni and Ratner, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…The combined contamination of groundwater by heavy metals and organics has become a serious problem worldwide, threatening both the natural ecosystem and human health [1]. Vanadium, a redox-sensitive metal, widely occurring in the Earth's crust, is employed in metallurgy, manufacturing, and petroleum refining industries [2], and is an efficient catalyst in the selective catalytic reduction of nitrogen oxides in exhaust gases [3]. Dissolution of vanadium-rich rocks and anthropogenic activities lead to the presence of vanadium in groundwater [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The raising background pattern of the diffractogram indicates the presence of a large number of substances, probably iron compounds, with a low degree of structure order. Other research also confirmed that iron compounds exist mainly in amorphous forms [13,35,36].…”
Section: Resultsmentioning
confidence: 65%